Pemilihan Ketua Rukun Tetangga dan Rukun Warga Berbasis Android di Dukuh Celeban Yogyakarta - Murti Retnowo; Wahyu Sri Utami; Ikrimach (Jurnal ABDI RAKYAT, 2024)
The impact of the spread of the Covid-19 virus, which is increasing every day, has resulted in restrictions on community activities in all fields including the election of the head of the affected neighbourhood’s unit (RT) and community unit (RW). citizens and a direct voting process are carried out. With the COVID-19 pandemic, the election of RT and RW heads cannot be carried out properly, therefore the author intends to create and implementation an information system for the election of RT and RW heads that can be used by all residents and can be carried out from the homes of each resident without having to conduct community meetings as usual. The system to be built is mobile-based so that it can be run through applications on Android-based smartphones. The choice of a mobile-based information system (Android) is because almost all citizens have an Android-based smartphone, besides that, an Android-based smartphone is also easy to operate.